Verbal neuropsychological functions in Aphasia: an integrative model - Vigliecca, Nora Silvana (2014)
A theoretical framework which considers the verbal functions of the brain under a multivariate and comprehensive cognitive model was statistically analyzed. A confirmatory factor analysis was performed to verify whether some recognized aphasia constructs can be hierarchically integrated as latent factors from a homogenously verbal test. The Brief Aphasia Evaluation was used. A sample of 65 patients with left cerebral lesions, and two supplementary samples comprising 35 patients with right cerebral lesions and 30 healthy participants were studied. A model encompassing an all inclusive verbal organizer and two successive organizers was validated. The two last organizers were: three factors of comprehension, expression and a “complementary” verbal factor which included praxia, attention, and memory; followed by the individual (and correlated) factors of auditory comprehension, repetition, naming, speech, reading, writing, and the “complementary” factor. By following this approach all the patients fall inside the classification system; consequently, theoretical improvement is guaranteed.